2014
DOI: 10.4103/2277-9175.139524
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin C on morphine self-administration in rats

Abstract: Background:Recent studies have shown that addiction may be caused by abnormality of neurotransmission in the brain. Two neurotransmitters that involve into morphine addiction are dopamine and glutamate. The glutamatergic and dopaminergic systems are also involved in morphine tolerance and morphine withdrawal syndrome signs. Ascorbic acid (AA), as the antioxidant releases from the glutamatergic neurons, modulates the action of the dopamine and glutamate systems. In this study, the effect of AA on morphine self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Repeated administration of opioids including morphine is known to damage cells and tissues through the generation of ROS and suppression of antioxidant genes resulting in opioid-induced disorders such as addiction and MAT [ 4 , 52 , 53 ]. The supplementation of antioxidants is shown to improve the disturbance of redox homeostasis induced by morphine [ 7 , 8 , 9 , 10 ]. To verify this phenomenon THP cells were treated either with MPDA, morphine, and MPDA@Mor with DMEM as a positive control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated administration of opioids including morphine is known to damage cells and tissues through the generation of ROS and suppression of antioxidant genes resulting in opioid-induced disorders such as addiction and MAT [ 4 , 52 , 53 ]. The supplementation of antioxidants is shown to improve the disturbance of redox homeostasis induced by morphine [ 7 , 8 , 9 , 10 ]. To verify this phenomenon THP cells were treated either with MPDA, morphine, and MPDA@Mor with DMEM as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently MPDA@Mor chronic administration significantly reduced TNF-α and NFkb protein levels in DRG compared with the morphine group ( Figure 7 c,d, red bars). Thus, we postulated that MPDA@Mor can alleviate MAT through the inhibitions of glial-derived pro-inflammatory cytokine activation which could be attributed to the antioxidant properties of MPDA, as the administration of exogenous antioxidants has been shown to attenuate MAT through the suppression of pro-inflammatory cytokine levels by several reports [ 7 , 8 , 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-administration of 1 g/kg vitamin C with morphine prevented the development of morphine tolerance and physical dependence in mice [ 101 ]. Intraperitoneal administration of 400 mg/kg vitamin C significantly decreased self-administration of morphine and withdrawal syndrome signs in rats [ 102 ]. Vitamin C itself was shown to have antinociceptive effects in mice (ED50 of 206 mg/kg).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been carried out in humans, but some small cohorts have shown reduced circulating vitamin C levels in chronic opioid users [ 12 , 13 ]. Treatment with vitamin C has been shown to decrease opioid withdrawal symptoms in guinea pigs [ 14 ], rats [ 15 ], and humans [ 16 , 17 ]. AA has been described as a solubilizing agent for street heroin base, although the amount of AA required is far below the amounts used in laboratory and clinical research settings [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%